2019
DOI: 10.1101/766600
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genetic “General Intelligence,” Objectively Determined and Measured

Abstract: It has been known for 115 years that, in humans, diverse cognitive traits are positively intercorrelated; this forms the basis for the general factor of intelligence (g). We directly test for a genetic basis for g using data from seven different cognitive tests (N = 11,263 to N = 331,679) and genome-wide autosomal single nucleotide polymorphisms. A genetic g factor accounts for 58.4% (SE = 4.8%) of the genetic variance in the cognitive traits, with trait-specific genetic factors accounting for the remaining 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 58 publications
(34 reference statements)
0
7
0
Order By: Relevance
“…The ability to control statistically for any variable, genetic or otherwise, depends on how well and comprehensively that variable is measured 91 . The tests of cognitive performance included in the Cog GWAS likely do not capture all genetic influences on all forms of cognitive ability across the lifespan 92 , 93 . Despite these limitations, our simplified and incomplete statistical separation of NonCog from Cog allowed us to test whether heritable traits other than cognitive ability influenced educational attainment and to explore what those traits might be.…”
Section: Discussionmentioning
confidence: 99%
“…The ability to control statistically for any variable, genetic or otherwise, depends on how well and comprehensively that variable is measured 91 . The tests of cognitive performance included in the Cog GWAS likely do not capture all genetic influences on all forms of cognitive ability across the lifespan 92 , 93 . Despite these limitations, our simplified and incomplete statistical separation of NonCog from Cog allowed us to test whether heritable traits other than cognitive ability influenced educational attainment and to explore what those traits might be.…”
Section: Discussionmentioning
confidence: 99%
“…Psychological and physical differences can be highly heritable but also highly malleable by the environment (e.g., height). Furthermore, in the United States, heritability-of-ability estimates vary as a function of social class (Giangrande et al, 2019), but this effect is not observed in Europe or Australia, which may be taken as a sign of greater socioeconomic inequality in the United States (Tucker-Drob & Bates, 2016).…”
Section: Genetics Of Cognitive Abilitymentioning
confidence: 99%
“…Early research on intelligence also contributed to advances in measurement and theory. While still a graduate student, Charles Spearman (1904) published a fundamentally important article establishing the tradition of measuring general intelligence ( g ) that continues to this day (de la Fuente, Davies, Grotzinger, Tucker-Drob, & Deary, 2019). Spearman correlated psychophysical sensitivity to pitch, weight, and light with teacher ratings of “common sense” and cleverness in 24 village children and with school performance in the classics, French, English, and mathematics in the upper class of a preparatory school ( N = 22).…”
mentioning
confidence: 99%
“…Some have used a single test, such as a Verbal Numerical Reasoning (Fluid Intelligence, FI) score or a reaction time (RT) score (Davies et al, 2016;Sniekers et al, 2017;Kievit et al, 2018;Lee et al, 2018;Savage et al, 2018). Others have extracted a 'g-factor' of general cognitive ability by aggregating several variables using Principal Component Analysis (PCA) or Confirmatory Factor Analysis (CFA; Lyall et al, 2016;Navrady et al, 2017;Cox et al, 2019;de la Fuente et al, 2021;Hepsomali and Groeger, 2021). However, this inconsistency in the definition of cognitive domains across different studies is a potential threat to replicability of the findings.…”
Section: Introductionmentioning
confidence: 99%